Role of Cu on hydrogen embrittlement behavior in Fe–Mn–C–Cu TWIP steel. (22nd June 2015) - Kwon, Young Jin; Lee, Taekyung; Lee, Junmo; Chun, Young Soo; Lee, Chong Soo
Abstract: The effect of a Cu addition on a hydrogen embrittlement (HE) was studied in Fe–17Mn-0.8C TWIP steels with 0–2 mass% of Cu. As-rolled and hydrogen-charged samples were investigated by examining their microstructures, tensile properties, fracture behaviors, and hydrogen-related characteristics. Diffusible hydrogen was mainly trapped at the grain boundaries in the present steels, the amount of which was similar regardless of the Cu composition. However, the Cu addition clearly enhanced the HE resistance of the alloys. It was revealed that the Cu addition did not change the HE mechanism but affected the HE rates. The hydrogen-charged steels exhibited heterogeneous intergranular fractures due to the limited diffusion of hydrogen. The mechanism of the retarded HE in Fe–Mn–C–Cu TWIP steels was the mitigation of the applied stress on grain boundaries and the uniform distribution of hydrogen. These mechanisms were wholly different from those reported in Fe–Mn–C–Al TWIP steels in spite of the similar improvements in the HE resistance. Highlights: HE properties of TWIP steels with various Cu compositions were investigated. Cu-added samples exhibit the high HE resistance. The Cu addition did not affect the HE mechanism but changed the HE rate. The effect of Cu addition on the HE rate was discussed in terms of crack initiation and propagation.